Phytochemical Analysis of Selected Indigenous Medicinal Plants used in Rwanda - Rwai Waweru, Wilson; Obado Osuwat, Lawrence; Karomo Wambugu, Francis (Journal of Pharmacognosy and Phytochemistry, 2017)
The medicinal properties exhibited by various medicinal plants are driven by the phytochemicals present in the plants. The purpose of this study was to identify the phytochemicals present in the six selected medicinal plants used in Rwanda. Standard procedures for phytochemical screening were used to test for the presence of various phytochemicals. All the selected medicinal plants were found to contain tannins and flavanoids, saponnis and phenols. Alkaloids were also present in all the selected plants except Aloe myriacantha and Eucalyptus camaldulensis. The study concluded that medicinal plants used in Rwanda possessed various phytochemicals that aids in the medicinal properties of the studied plants.
Keywords: Phytochemical; Vernonia mygdalina; Zehneria scabra; Leonotis nepetifolia; Tetradenia riparia; Aloe myrianantha